Reception Aesthetics of Religious Moderation Values in Linggabuana’s Serat Carub Kandha - Firdausi, Muhammad Anwar; Rosyidah, Inayatur; Hambali, Gufron; Fatimah, Siti (UIN Maulana Malik Ibrahim Malang, 2023)
The diversity of readers' responses in literary works is called reception aesthetics. This study aims to elucidate the readers’ response and the reception aesthetics towards the values of religious moderation in Serat Carub Kandha by Prince Linggabuana. Employing the research design of the synchronic experimental reception method, the data collection utilized note-taking and literature study techniques. It involved twenty respondents of Islamic university students as the readers. The data analysis technique used reader criteria assessment and Hans Robert Jauss' theory concerning the reader's experience of the novel, horizon of expectations, aesthetic distance, the spirit of the times, literary series, and literary history. The chosen manuscript was Serat Carub Kandha Pupuh Mijil as the fifth branch of the story. The results demonstrated that the noble value readers capture is in the form of religious moderation values. They are tolerance (tasamuh), neutral (tawassuth), uprightness (i’tidal), deliberation (al-shura), anti-violence (la' unf), and culture friendly (i'tibar al-'urf). These are manifested through respect for diversity and multicultural in the part of allowing residents to establish Islamic learning centers even though the Padjajaran kingdom practiced Buddhism. Notably, the wife of Prince Linggabuana, Dewi Subang Kranjang, embraced Islam, while his three sons secretly studied Islam with Sheikh Quro'. Keberagaman tanggapan atau respon pembaca pada karya sastra disebut estetika resepsi. Penelitian ini bertujuan untuk mendeskripsikan tanggapan dan estetika resepsi pembaca terhadap nilai-nilai moderasi beragama dalam Serat Carub Kandha karya Pangeran Linggabuana. Dengan memakai rancangan penelitian metode resepsi sinkronis eksperimental, pengumpulan data menggunakan teknik simak catat dan studi kepustakaan. Penelitian ini melibatkan dua puluh mahasiswa universitas Islam sebagai pembaca. Teknik analisis data menggunakan penilaian kriteria pembaca dan teori Hans Robert Jauss yang meliputi pengalaman pembaca terhadap novel, horizon harapan, jarak estetik, semangat zaman, rangkaian sastra dan sejarah sastra. Naskah yang dipilih yaitu Serat Carub Kandha Pupuh Mijil, yang merupakan cabang cerita yang kelima. Berdasarkan hasil penelitian, nilai luhur yang bisa ditangkap pembaca berupa nilai-nilai moderasi beragama. Nilai tersebut meliputi tasamuh (toleransi), tawassuth (netral), i’tidal (lurus), al-shura (musyawarah), la' unf (anti kekerasan), dan i'tibar al-'urf (ramah budaya). Hal ini tercermin dalam penghormatan akan keberagaman dan multikultural pada bagian diperbolehkannya penduduk membangun pusat kegiatan belajar agama Islam meskipun kerajaan Padjajaran beragama Buddha. Bahkan istri Pangeran Linggabuana, Dewi Subang Kranjang beragama Islam, sementara ketiga putranya diam-diam mempelajari Islam kepada Syeikh Quro’